(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background Objective: To assess T3, T4 &TSH levels and prevalence of thyroid disorders in the suspected patients received at collection centers of Aga Khan Lab in Southern Punjab districts. Place and Duration: A retrospective study was conducted from July 2012 to December 2012 at Multan Stat Laboratory of Aga Khan University Hospital. Methods: 1784 suspected patients were evaluated for thyroid hormonal assay-tri iodo thyronine (T3), tetra iodo thyronine (T4) and thyroid stimulating hormone (TSH) by using cobas kits on Cobas e 411 immunoassay auto analyzer using electrochemiluminescence immunoassay(ECLIA) technique. Results: Out of total one thousand seven hundred and eighty four cases of suspected individuals,472 (26.45%) were males and 1312(73.54%) were females. Out of total ,518(29.03%)subjects including139 (26.83%) males and (73.16%) 379 females showed thyroid dysfunction with male to female ratio 1:2.73. Of these 1784 cases, 357 (20.01%) were in age group of < 20 years, 1189 (66.65%) were in 21-54 years, and 238 (13.34%) were in age group of > 55 years. . Most common thyroid disorder found was hyperthyroidism (14.18 ) followed by hypothyroidism (6.73%) which was followed by subclinical hyperthyroidism (4.87%) and subclinical hypothyroidism (3.25%) . Conclusion: The prevalence of thyroid dysfunction was very high (29.03 %) with hyperthyroidism (14.18%) being most common. Females were more affected